The Analysis of Legal Protection for the Practice of Adding Watermarks in Graphic Design Products - Muhamad Noval Arahman; Fifiana Wisnaeni (Law Development Journal, 2023)
. Intellectual Property Rights (IPR) is born from an individual's recognition of his intellectual abilities, so that each of his works is directly attached to the creator. A work of art can be created by anyone, especially activists in the art world such as singers, writers, designers, photographers and so on. In its development, creators always find the latest variations and innovations for work. These innovations can be of various kinds and can result in good or bad, can harm other parties or not harm other parties. In one's profession a Graphic Designer always produces graphic design work that develops every year and follows market demand. The protection of graphic design products is also carried out by several owners, those who understand the Copyright Law must register their products with the Directorate General of Intellectual Property Rights by following the existing procedures. But on the other hand, there are also some copyright owners who do not register, but instead provide watermarks or watermarks in their works. This study aims to provide an understanding for those who carry out watermarking actions by using juridical and normative methods by prioritizing library-based legal research whose sources come from secondary data which is then applied to the core problem of this research, namely Watermarking in Graphic Design which focuses on the legal protection of the parties. This research provides an understanding of how the act of affixing a watermark gets legal protection according to Act No. 28 of 2016 concerning Copyright